THE ROLE OF UNDEREMPLOYMENT IN TURNOVER INTENTION THROUGH JOB DEPRIVATION AND JOB STRESS: A MULTIPLE MEDIATION MECHANISM - Afzal, Hafiza Fatima; Islam, K. M. Anwarul; Ismail, Adnan; Tahir, Muhammad Yasir; Zohaib, Muhammad; Riaz, Jamshaid; Ismail, Muhammad (International Journal of Business and Management Future, 2021)
Mainly determination focused on examining the ’underemployment ’via exploring its relationship with ’turnover intention’. Furthermore, the other variable ’job deprivation’ was analyzed as a mediator for said relationship. In addition, the moderating role of ’job stress’ was also premeditated for underemployment and job deprivation. Our targeted audience for this research article was "Traffic Police Wardens" (TPW). We have collected sample data from three cities of Punjab province (1) Lahore, (2) Multan, & (3) Bahawalpur. The population was the whole of Pakistan. Data was collected with the help of a questionnaire via cross-sectional data. 600 were distributed and received N= 499 which were completed by all aspects. The CFA was carried out in SEM (Structural Equation Model), whereas the data was analyzed in SPSS, on the 22nd version. The statistical analysis of this research article retrospection that Cronbach alpha (α) > 0.72 among all variables which are presenting the highest reliability. Further, we check the correlation of the variables among each other, and we found that the dependent variable (DV) is positively correlated to independent variables (IV) because ’underemployment in turnover intention is positively correlated with job deprivation and job stresses. Results of this research article demonstrate that correlation values were r = >0.5 and Regression’s values p = <0.01. It indicates that there was a positive and significant effect of underemployment on turnover intention. The findings also support job deprivation as an intervening mechanism for the relation of underemployment and turnover intention. In addition, job stress acts as a moderator for the relationship between underemployment and job deprivation. The study concludes with a discussion, limitations, and future research directions including implications both for theory and practitioners. JEL Classification Codes: O15.